Somos, sem modéstia, [...] um homem de teatro : os manuscritos de Coriolano Benício como documentos (auto) biográficos - Silveira, João Paulo Borges da (2013)
This essay focuses on (auto) biographic documents belonging to Coriolano Mário Araújo Benício (1911-1984) personal archives, citizen of Rio Grande whose personnel and professional trajectories were dedicated to his county's cultural and artistics scenes. This study starts with a restlessness due to little knowledge about Coriolano Benicio figure and personal files in Rio Grande. The research is justified by academic novelty, as Coriolano Benicio personal and professional trajectories through his files have never been explored. Once manuscripts from his personal archives features (auto) biographical information, which Coriolano recorded traces of his life's trajectory, these documents, therefore, are holders of it's owner's memories, while also represent important elements to comprehend the collective artistic memory of the city of Rio Grande